Development of coliform test kit for microbiological quality water - Panthipamporn, Theera (Bulletin of Applied Sciences, 2016)
Coliform bacteria is a microbiological indicator of water quality. However, water samples sometimes cannot be sent for test such bacteria on time. Therefore, the qualitative test kit for coliforms in water was developed as a preliminary investigation. The test kit was developed under the concept that coliform bacteria can use lactose and produce acid and gas within 24-48 hours. It was found that lauryl sulfate broth media at a concentration of 3 times with addition of bromocresol purple 0.01 g/l gave most effective result at 20 ml water sample. Coliform bacteria were detected by the changing of color from clear purple to turbid yellowish-liquid. Detection performance comparing of test kit with standard method (AWWA, 2012) and commercial test kit developed by Department of Health using 49 water samples (29 non-potable water and 20 potable water) showed equal effective and detection limit equal to 2.2 MPN/100 mL of AWWA method. Hence, the test kit can be recommended for detection of presumptive coliform bacteria in potable water in the field.